Acute responses of hypertrophic- and neural strength exercise on endurance performance and running economy - Auvinen, E.-P.; Mikkola, J.; Doma, K.; Ahtiainen, J. P. (19th International Symposium "Modern Science and Practice for Strength and Endurance Training" October 10-12, 2018, 2020)
Strength training have been shown to be beneficial for endurance performance (1). Training for both endurance- and strength may cause greater improvements in endurance performance compared to endurance training alone (2). However, if appropriate periodization is not accounted for, strength training may also hinder optimal endurance development (3). Examining the acute effects of strength training on running performance may contribute to the body of knowledge on the interaction between the two training modes. Thus, the aim of this study was to examine effects of hypertrophic- (HSE) and neural strength exercise (NSE) on endurance performance 48 hours post exercise.